Laparoscopic repair of femoral hernia - Yang, Xue-Fei (Ann Transl Med, 2016)
Laparoscopic repair of inguinal hernia is mini-invasive and has confirmed effects. Femoral hernia could be repaired through the laparoscopic procedures for inguinal hernia. These procedures have clear anatomic view in the operation and preoperatively undiagnosed femoral hernia could be confirmed and treated. Lower recurrence ratio was reported in laparoscopic procedures compared with open procedures for repair of femoral hernia. The technical details of laparoscopic repair of femoral hernia, especially the differences to laparoscopic repair of inguinal hernia are discussed in this article.